Abū l-Hudà al-Ṣayyādī (1850-1909), the niqābat al-ašrāf, and Sufism between Sunnah and Šīʿah in Late Ottoman Iraq (Šarīfism in Modernity I) - Jordan, David (Oriente moderno, 2023)
During the late nineteenth and early twentieth century, the Ottoman state’s efforts to centralize the Syndicate of Prophetic Descendants (niqābat al-ašrāf) was paralleled by the massive growth of Prophetic descendants (sādah and ašrāf) and the mass conversion to the Šīʿah among the tribes in the Iraqi provinces. This contribution aims to shed new light on the role of Abū l-Hudà al-Ṣayyādī (1266/1850-1327/1909), the imperial naqīb al-ašrāf and paramount šayḫ and architect of the Sunnī Rifāʿiyyah Sufi order, in this context. Analyzing a selection of Ṣayyādī’s publications on genealogies, Sufi doctrine, and poem collections, the article focuses on his contribution to the emergence of a special subgroup of Prophetic descendants in the Arab tribal landscape, namely al-sādah al-rifāʿiyyah, and on the significance of his genealogical constructions for his understanding of Sunnī Islam as distinct from Šīʿism.